Serum Biochemical Markers of Liver Fibrosis - Irwan Setiabudi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2006)
Progressive liver fibrosis with development of cirrhosis is a feature of almost all chronic liver diseases. Carriers of hepatitis B and C virus are at increased risk of developing cirrhosis, hepatic decompensation/insufficiency, hemorrhage, and hepatocellular carcinoma (HCC). Therefore, periodic evaluations of these patients are necessary. Fibrosis is deleterious but variable consequence of chronic inflammation. It is characterized by deposition of extra cellular matrix component leading to distortion of hepatic architecture with impairment of liver microcirculation and liver cell function. Although liver biopsy is the gold standard for assessment of liver fibrosis, it has several disadvantages. Considering these limitations and patient redundancy to undergo liver biopsy, it is vital that non -invasive predictors/ Methods for assessment of liver fibrosis be developed and validated. Application of this Method could be used to evaluate the efficacy of treatment, which is a simple and meaningful way. Recently, clinical investigators have been searching for noninvasive serum markers of fibrosis, which have the following characteristics: they must be reliable, accurate, reproducible and easy to perform. Several markers or combination of several markers have shown promise for the detection of advanced fibrosis, although their sensitivities for detecting milder fibrosis are poor. Non -invasive laboratory bio-markers of liver fibrosis might be applied to patients who either have contra-indication or refuse liver biopsy for management of their chronic liver diseases. Keywords: hepatitis B virus, liver fibrosis, liver biopsy